The Study of Road Accident Trends at Johor State Road Using Analythical Hierarchy Process (AHP) and Geoda - Mohd Bukari, Saifullizan; Mohd Fadzli, Nur Azreen Farahin (Recent Trends in Civil Engineering and Built Environment, 2021)
Road traffic accidents are usually happened and keep increasing year by year in Malaysia. It will give a adverse impact at the road also to the road user. It has been announced every day in the social media, television broadcast, radio and newspaper. There are several causes that contribute to the accident such as faulty vehicle, uneven roads, driver behavior and many more. So, with all these causes, it might be the reason why the road accidents keep on increasing. The purpose of this case study is to determine the highest road accident ranking based on the types of injuries at the state road, Johor. Then, another purpose is to identify the current traffic accident trends. To accomplish the first purpose of this study, secondary data which is from Balai Polis Traffic, Batu pahat will be used to get an accident data and the Analythical Hierarchy Process (AHP) will be proceed to find the road accident ranking based on the types of injuries. This case study will use the five years of road accident data which is from the year 2016 until October 2020. Next, Geoda will be used to insert the data about the road accident trends. With those analysis, the highest road accident ranking based on the types of injuries and the road accident trends can be obtained and achieve all the objective of this case study. Besides that, it will be useful as a reference to any party in the future for the road traffic management.